A tale of two regions: investment in Latin America and East Asia - Agosín, Manuel (Estudios de Economía, 2016)
This paper examines why the investment rates of Latin American countries have been so low, in comparison with those of the fast growing East Asian countries. First, the paper compare the private and public investment ratios of eight Latin American countries, and their likely determinants, with those of five dynamic Asian countries. Second, it estimates an econometric model for the ratio of private investment to GDP in Latin American and Asian countries, respectively. The econometric results and a casual examination of the data suggest that the causes for the poor performance of private investment in Latin America relative to Asia are: considerably slower economic growth.